2018
DOI: 10.1038/s41467-018-06435-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of homologous recombination repair at single collapsed replication forks

Abstract: Homologous recombination (HR) is a crucial pathway for the repair of DNA double-strand breaks. BRCA1/2 breast cancer proteins are key players in HR via their mediation of RAD51 nucleofilament formation and function; however, their individual roles and crosstalk in vivo are unknown. Here we use super-resolution (SR) imaging to map the spatiotemporal kinetics of HR proteins, revealing the interdependent relationships that govern the dynamic interplay and progression of repair events. We show that initial single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 98 publications
(144 reference statements)
2
65
1
Order By: Relevance
“…RAD52 acts as mediator of ssDNA/RAD51 filaments during seDSB repair by HR in human cells, a role where it can be replaced by BRCA2 [14]. The severe TMZ sensitivity induced by loss of RAD52 and its strong ability to rescue the defective phenotypes associated with XAB2 depletion suggest that RAD52 also exerts a function independently of RAD51, in line with a previous report [15].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…RAD52 acts as mediator of ssDNA/RAD51 filaments during seDSB repair by HR in human cells, a role where it can be replaced by BRCA2 [14]. The severe TMZ sensitivity induced by loss of RAD52 and its strong ability to rescue the defective phenotypes associated with XAB2 depletion suggest that RAD52 also exerts a function independently of RAD51, in line with a previous report [15].…”
Section: Discussionsupporting
confidence: 88%
“…8). As XAB2 is present at seDSBs, we propose that XAB2 acts 14 via a direct mechanism to promote Ku eviction from resected seDSBs. The molecular details of this novel pathway and its interplay with the ATM-dependent pathway in counteracting Ku accumulation merit further exploration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Validating U-DNA-Seq data, we found that U-DNA staining shows significant colocalization with staining for both chromatin markers; H3K36me3 and H3K27me3, based on cross-pair correlation analysis of the super-resolution images as shown in Figure 7C-D. The rate of colocalization, as determined by the interaction factor (IF) value (Bermudez-Hernandez et al, 2017; Whelan et al, 2018), was statistically significant between the uracil signal and both chromatin markers in each case of drug treatment, when compared to the non-treated sample as well as to a generated set of random distribution patterns of these chromatin markers.…”
Section: Resultsmentioning
confidence: 86%
“…The interaction factor (IF) quantifies the colocalization of red and green foci within a cell nucleus by measuring the area of overlap between the two sets of foci (Bermudez-Hernandez et al, 2017; Whelan et al, 2018). The positions of the green foci are then randomized and the overlap between the two colours is measured again.…”
Section: Methodsmentioning
confidence: 99%